The management of congenital diaphragmatic hernia - Mihaela Plotogea; Claudia Mehedintu; Valentin Nicolae Varlas; Aida Petca; Radu Nicolae Mateescu; Antoine Edu; Vlad Dima; Cristina Veronica Andreescu; Gabriel Marina (Amaltea Medical Publishing House, 2022)
Congenital diaphragmatic hernia (CDH) is a structural birth defect that with varying degrees of severity that results in significant neonatal morbidity and mortality. CDH occurs in 1:2,500 live births, and despite the advances in prenatal diagnosis and neonatal intensive care, the mortality and morbidity rate in infants with CDH is significant. In this article, we tried to summarize the main modalities of diagnosis, prognosis and medical treatment in CDH cases, found in specialty literature.